Estimating the Effects of the English Rule on Litigation Outcomes - Helland, Eric; Yoon, Jungmo (The Review of Economics and Statistics, 2017)
The English rule prescribes that the loser of a lawsuit pays the winner's litigation costs. Previous research on the English rule finds that plaintiffs win more often at trial, receive higher awards, and receive larger settlements. Theory predicts that the English rule discourages settlement by raising the threshold payment necessary for settlement. In this paper, we reexamine the Florida experiment with the English rule by placing bounds on the selection effects. We find that the mean and median settlement amount increases. Collectively these findings are consistent with the predictions of the simplest models of the English rule's impact.